Disclosure as a Mechanism to prevent Market Failure - Marotta-Wurgler, Florencia (2017)
Regulators often address the potential for onesided standard form contracts by requiring extra disclosure of the terms. Despite its ubiquity, for a disclosure regime to be effective, it must increase readership of contracts beyond a nontrivial rate, and, in addition, individuals must be willing to change their decisions conditional on what they read. I follow the clickstream of 47,399 households to 81 Internet software retailers to test whether those who shop for software online are more likely to read the license agreement when it is more prominently disclosed. I find that the degree of disclosure has almost no impact on the rate at which consumers read license agreements. Moreover, those who do read are equally likely to purchase the software product regardless of the onesidedness of the contract. The results suggest that mandating disclosure online is unlikely, on its own, to put pressure on sellers. KEYWORDS: market failures, information disclosure, market, technological products, consumers. JEL CODE: E65, D46